2018
DOI: 10.1080/14737159.2018.1439382
|View full text |Cite
|
Sign up to set email alerts
|

The breast tumor microenvironment: role in cancer development, progression and response to therapy

Abstract: Numerous clinical and pre-clinical studies have provided ample evidence supporting that the tumor microenvironment plays a significant role during breast cancer development, progression and in determining the therapeutic response. Areas covered: This review focuses on the evolving concept of the microenvironment as the critical participant in each step of the multi-stage process of malignant progression. Currently, only a small number of molecules form part of routine molecular diagnostics in breast caner, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 231 publications
1
103
0
Order By: Relevance
“…On one side, tumor cells directly interact each other and sculpt the ECM by releasing a variety of proteins that act as autocrine or paracrine factors influencing cancer and non-cancer cell proliferation, differentiation, and survival [ 1 ]. On the other hand, released factors from cancer-associated fibroblasts (CAF) and adipocytes (CAA) contribute to the tumorigenic phenotype of pre-malignant and malignant epithelial cells [ 4 ] promoting tumor cell proliferation, invasiveness, and growth. In addition, CAF-released factors influence the development of therapy resistance by inducing anti-apoptotic mechanisms in both estrogen receptor α positive (ERα+) and negative (ERα−) breast cancer cells exposed to anti-cancer drugs [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On one side, tumor cells directly interact each other and sculpt the ECM by releasing a variety of proteins that act as autocrine or paracrine factors influencing cancer and non-cancer cell proliferation, differentiation, and survival [ 1 ]. On the other hand, released factors from cancer-associated fibroblasts (CAF) and adipocytes (CAA) contribute to the tumorigenic phenotype of pre-malignant and malignant epithelial cells [ 4 ] promoting tumor cell proliferation, invasiveness, and growth. In addition, CAF-released factors influence the development of therapy resistance by inducing anti-apoptotic mechanisms in both estrogen receptor α positive (ERα+) and negative (ERα−) breast cancer cells exposed to anti-cancer drugs [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic tumor tissues, the higher proportions of CD4 + and CD8 + T cells, the better long-term prognosis for patients [40]. In breast carcinoma, annexin1 promoted polarization of M1 macrophages and induced pro-inflammatory genes [41]. Nevertheless, it was reported that the higher numbers of T or B cells, the worse capsular and perineural invasion in prostate cancer [42].…”
Section: Kinase Targets Of Hub Genesmentioning
confidence: 99%
“…These sites are known as pre-metastatic niches (PMNs). One of the main factors regarding metastasis is the generation of these preordained areas which enable the cells to succeed in their migration [8,9,15,16] . In addition, drugresistant clones in the primary tumor are more competent to undergo epithelial-mesenchymal transition (EMT) and present higher probabilities to reach a favorable PMN [5] .…”
Section: Tumor Microenvironment and Therapy Resistancementioning
confidence: 99%